Exploring the Link between Athletic Identity, Self-compassion, Communication, and Mental Toughness of Table Tennis Student-Athletes - Maridette Joyce D. Maranan; Arnulfo V. Lopez (Universidad de Granada, 2021)
Table tennis student-athletes should be mentally tough as they train and perform under extreme pressure. It is essential to identify other mental skills that will aid mental toughness development. Accordingly, the study focused on assessing athletic identity, self-compassion, and intra-team communication. The relationship between the constructs was also explored. A multi-part questionnaire was fielded to 230 college student-athletes participating in table tennis singles event. Findings indicate high levels of athletic identity and intra-team communication among the participants; while moderate levels for self-compassion and mental toughness. Structural equation modeling revealed the dynamic relationship between the constructs. On one hand, self-compassionate participants who highly recognize their role as athletes, and communicate with the team are more mentally tough. On the other hand, uncompassionate self-responding lead student-athletes to become mentally weak. The study provides useful insights for practitioners in designing mental skills training geared towards optimal functioning and psychological wellness of young athletes.